Behavioral Measures of Cochlear Gain Reduction Depend on Precursor Frequency, Bandwidth, and Level - DeRoy Milvae, Kristina; Strickland, Elizabeth A. (Frontiers in Neuroscience, 2021)
Sensory systems adjust to the environment to maintain sensitivity to change. In the auditory system, the medial olivocochlear reflex (MOCR) is a known physiological mechanism capable of such adjustment. The MOCR provides efferent feedback between the brainstem and cochlea, reducing cochlear gain in response to sound. The perceptual effects of the MOCR are not well understood, such as how gain reduction depends on elicitor characteristics in human listeners. Physiological and behavioral data suggest that ipsilateral MOCR tuning is only slightly broader than it is for afferent fibers, and that the fibers feed back to the frequency region of the cochlea that stimulated them. However, some otoacoustic emission (OAE) data suggest that noise is a more effective elicitor than would be consistent with sharp tuning, and that a broad region of the cochlea may be involved in elicitation. If the elicitor is processed in a cochlear channel centered at the signal frequency, the growth of gain reduction with elicitor level would be expected to depend on the frequency content of the elicitor. In the current study, the effects of the frequency content and level of a preceding sound (called a precursor) on a signal are examined. The results show that signal threshold increases with increasing precursor level at a shallower slope for a tonal precursor at the signal frequency than for a tonal precursor nearly an octave below the signal frequency. A broadband noise was only slightly more effective than a tone at the signal frequency, with a relatively shallow slope similar to that of the tonal precursor at the signal frequency. Overall, these results suggest that the excitation at the signal cochlear place, regardless of elicitor frequency, determines the magnitude of ipsilateral cochlear gain reduction, and that it increases with elicitor level.